Exercise algebra.manipulation.exponential.equation

Description
solve exponential equation algebraically

Derivations

1.

2^x == 16*sqrt 2
algebra.manipulation.exponents.factor-as-power
2^x == 2^4*sqrt 2
algebra.manipulation.exponents.write-as-power
2^x == 2^4*2^(1/2)
algebra.manipulation.exponents.add-exponents
2^x == 2^(9/2)
algebra.manipulation.exponents.equation.same-base
x == 9/2

2.

2^(x+2) == 1/4
algebra.manipulation.exponents.factor-as-power
2^(x+2) == 1/2^2
algebra.manipulation.exponents.reciprocal
2^(x+2) == (2^2)^(-1)
algebra.manipulation.exponents.mul-exponents
2^(x+2) == 2^(-2)
algebra.manipulation.exponents.equation.same-base
x+2 == -2
algebra.equations.coverup.onevar.plus
x == -4

3.

3^(x-1) == 81
algebra.manipulation.exponents.factor-as-power
3^(x-1) == 3^4
algebra.manipulation.exponents.equation.same-base
x-1 == 4
algebra.equations.coverup.onevar.minus-left
x == 5

4.

3^(x+5) == 243/sqrt 3
algebra.manipulation.exponents.factor-as-power
3^(x+5) == 3^5/sqrt 3
algebra.manipulation.exponents.reciprocal
3^(x+5) == 3^5*sqrt 3^(-1)
algebra.manipulation.exponents.write-as-power
3^(x+5) == 3^5*(3^(1/2))^(-1)
algebra.manipulation.exponents.mul-exponents
3^(x+5) == 3^5*3^(-1/2)
algebra.manipulation.exponents.add-exponents
3^(x+5) == 3^(9/2)
algebra.manipulation.exponents.equation.same-base
x+5 == 9/2
algebra.equations.coverup.onevar.plus
x == -1/2

5.

5^(2-x) == 1/25
algebra.manipulation.exponents.factor-as-power
5^(2-x) == 1/5^2
algebra.manipulation.exponents.reciprocal
5^(2-x) == (5^2)^(-1)
algebra.manipulation.exponents.mul-exponents
5^(2-x) == 5^(-2)
algebra.manipulation.exponents.equation.same-base
2-x == -2
algebra.equations.coverup.onevar.minus-right
x == 4

6.

3^(2*x) == 1/9
algebra.manipulation.exponents.factor-as-power
3^(2*x) == 1/3^2
algebra.manipulation.exponents.reciprocal
3^(2*x) == (3^2)^(-1)
algebra.manipulation.exponents.mul-exponents
3^(2*x) == 3^(-2)
algebra.manipulation.exponents.equation.same-base
2*x == -2
algebra.equations.coverup.times
x == -1

7.

3^(1-3*x) == 81
algebra.manipulation.exponents.factor-as-power
3^(1-3*x) == 3^4
algebra.manipulation.exponents.equation.same-base
1-3*x == 4
algebra.equations.coverup.onevar.minus-right
3*x == -3
algebra.equations.coverup.times
x == -1

8.

3^(3*x-2) == 3*sqrt 3
algebra.manipulation.exponents.write-as-power
3^(3*x-2) == 3*3^(1/2)
algebra.manipulation.exponents.simple-add-exponents
3^(3*x-2) == 3^(3/2)
algebra.manipulation.exponents.equation.same-base
3*x-2 == 3/2
algebra.equations.coverup.onevar.minus-left
3*x == 7/2
algebra.equations.coverup.times
x == 7/6

9.

5*2^(x-1) == 20*sqrt 2
algebra.equations.coverup.times
2^(x-1) == 4*sqrt 2
algebra.manipulation.exponents.factor-as-power
2^(x-1) == 2^2*sqrt 2
algebra.manipulation.exponents.write-as-power
2^(x-1) == 2^2*2^(1/2)
algebra.manipulation.exponents.add-exponents
2^(x-1) == 2^(5/2)
algebra.manipulation.exponents.equation.same-base
x-1 == 5/2
algebra.equations.coverup.onevar.minus-left
x == 7/2

10.

6*5^(2-x) == 150
algebra.equations.coverup.times
5^(2-x) == 25
algebra.manipulation.exponents.factor-as-power
5^(2-x) == 5^2
algebra.manipulation.exponents.equation.same-base
2-x == 2
algebra.equations.coverup.onevar.minus-right
x == 0

11.

2*7^(4*x-1) == 98
algebra.equations.coverup.times
7^(4*x-1) == 49
algebra.manipulation.exponents.factor-as-power
7^(4*x-1) == 7^2
algebra.manipulation.exponents.equation.same-base
4*x-1 == 2
algebra.equations.coverup.onevar.minus-left
4*x == 3
algebra.equations.coverup.times
x == 3/4

12.

8*3^(5-2*x) == 72*sqrt 3
algebra.equations.coverup.times
3^(5-2*x) == 9*sqrt 3
algebra.manipulation.exponents.factor-as-power
3^(5-2*x) == 3^2*sqrt 3
algebra.manipulation.exponents.write-as-power
3^(5-2*x) == 3^2*3^(1/2)
algebra.manipulation.exponents.add-exponents
3^(5-2*x) == 3^(5/2)
algebra.manipulation.exponents.equation.same-base
5-2*x == 5/2
algebra.equations.coverup.onevar.minus-right
2*x == 5/2
algebra.equations.coverup.times
x == 5/4

13.

2^x-7 == 9
algebra.equations.coverup.minus-left
2^x == 16
algebra.manipulation.exponents.factor-as-power
2^x == 2^4
algebra.manipulation.exponents.equation.same-base
x == 4

14.

4^(3*x)+5 == 69
algebra.equations.coverup.plus
4^(3*x) == 64
algebra.manipulation.exponents.factor-as-power
(2^2)^(3*x) == 64
algebra.manipulation.exponents.factor-as-power
(2^2)^(3*x) == 2^6
algebra.manipulation.exponents.mul-exponents
2^(6*x) == 2^6
algebra.manipulation.exponents.equation.same-base
6*x == 6
algebra.equations.coverup.times
x == 1

15.

7*3^(2*x+1) == 189
algebra.equations.coverup.times
3^(2*x+1) == 27
algebra.manipulation.exponents.factor-as-power
3^(2*x+1) == 3^3
algebra.manipulation.exponents.equation.same-base
2*x+1 == 3
algebra.equations.coverup.onevar.plus
2*x == 2
algebra.equations.coverup.times
x == 1

16.

5*2^(1-4*x)+11 == 51
algebra.equations.coverup.plus
5*2^(1-4*x) == 40
algebra.equations.coverup.times
2^(1-4*x) == 8
algebra.manipulation.exponents.factor-as-power
2^(1-4*x) == 2^3
algebra.manipulation.exponents.equation.same-base
1-4*x == 3
algebra.equations.coverup.onevar.minus-right
4*x == -2
algebra.equations.coverup.times
x == -1/2

17.

5^(x-4) == (1/5)^(2*x+1)
algebra.manipulation.exponents.reciprocal
5^(x-4) == (5^(-1))^(2*x+1)
algebra.manipulation.exponents.mul-exponents
5^(x-4) == 5^(-2*x-1)
algebra.manipulation.exponents.equation.same-base
x-4 == -2*x-1
algebra.equations.linear.var-left, term=(-2)*x
3*x-4 == -1
algebra.equations.coverup.onevar.minus-left
3*x == 3
algebra.equations.coverup.times
x == 1

18.

7^(1-2*x) == 1
algebra.manipulation.exponents.equation.equals-one
1-2*x == 0
algebra.equations.coverup.onevar.minus-right
2*x == 1
algebra.equations.coverup.times
x == 1/2

19.

4^(2*x-3) == 2*sqrt 2
algebra.manipulation.exponents.factor-as-power
(2^2)^(2*x-3) == 2*sqrt 2
algebra.manipulation.exponents.write-as-power
(2^2)^(2*x-3) == 2*2^(1/2)
algebra.manipulation.exponents.mul-exponents
2^(2*(2*x-3)) == 2*2^(1/2)
algebra.manipulation.exponents.simple-add-exponents
2^(2*(2*x-3)) == 2^(3/2)
algebra.manipulation.exponents.equation.same-base
2*(2*x-3) == 3/2
algebra.equations.linear.distr-times
4*x-6 == 3/2
algebra.equations.coverup.onevar.minus-left
4*x == 15/2
algebra.equations.coverup.times
x == 15/8

20.

2*9^(1-2*x) == 6*sqrt 3
algebra.equations.coverup.times
9^(1-2*x) == 3*sqrt 3
algebra.manipulation.exponents.factor-as-power
(3^2)^(1-2*x) == 3*sqrt 3
algebra.manipulation.exponents.write-as-power
(3^2)^(1-2*x) == 3*3^(1/2)
algebra.manipulation.exponents.mul-exponents
3^(2*(1-2*x)) == 3*3^(1/2)
algebra.manipulation.exponents.simple-add-exponents
3^(2*(1-2*x)) == 3^(3/2)
algebra.manipulation.exponents.equation.same-base
2*(1-2*x) == 3/2
algebra.equations.linear.distr-times
2-4*x == 3/2
algebra.equations.coverup.onevar.minus-right
4*x == 1/2
algebra.equations.coverup.times
x == 1/8